Is Jesus Palestinian? Palestinian Christian Perspectives on Judaism, Ethnicity and the New Testament. Issue 2 (November 2014) - Sandford, Michael J.
<x xml:space="preserve">Abstract</x> This article examines the views of eight prominent Palestinian Christians about Jesus' relationship to Judaism, and Jesus' relationship to contemporary Palestinian identity. These questions are explored within the context of two significant political phenomena: the emphasis on the Jewishness of Jesus within Western biblical studies and theology in the past four decades, and the prevalence of defamatory accusations of anti-Semitism against Palestinian Christians by their critics. This study offers a unique perspective on the question of the identity of the figure of Jesus within the context of the Palestine/Israel conflict, and demonstrates the geopolitical significance of the question of Jesus' relationship with Judaism for both Christians and Jews.